Potret Keberagamaan dalam Menciptakan Harmonisasi Masyarakat Dusun Sumberejo Desa Jambu Kecamatan Kayen Kidul - Ika Silviana; Syarifa Fitrotul Laila; Lia Hilyatul Masrifah (Canonia Religia)
This research focuses on the portrait of religiousness in a plural society in Sumberejo Hamlet, Kayen Kidul, Kediri Regency. The community consists of adherents of Islam, Christianity, Catholicism, and Hinduism who live side by side to create harmony in religion. This study uses a descriptive qualitative approach with data mining techniques, namely observation techniques, interviews, documentation, and audiovisuals. Determination of the subject is done using a purposive sampling technique, namely by taking samples based on criteria for adherents of each religion. This study was analyzed using Pierre Bourdieu's habitus theory as an analytical tool to dissect the phenomenon of harmony in the diversity of the Sumberejo Hamlet community. The results of this research show that the harmony formed in a plural society is caused by the habitus owned by the community through carrying out social activities together and participating in religious activities of other religions. Tolerance supported by social, economic, cultural and symbolic capital can create wealth and diversity in local culture.